A New Technique for Microvascular Anastomosis: Eversion with 3 Horizontal Mattress Sutures - Orak, I.; Gun̈eren, E.; Yíldíz, L. (Lippincott Williams & Wilkins, 2006)
In our experimental study of a new microvascular anastomosis technique, we divided 30 Wistar albino rats into 2 groups. We performed the classic interrupted suture anastomosis technique in group 1 (n = 15) and our new technique, using 3 horizontal mattress sutures, in group 2 (n = 15). We checked patency immediately following anastomosis, at the end of the first hour, and at the end of the third week postanastomosis.While the patency rates for both techniques were 100% at the end of the first hour, the respective values were 100% and 93.4% by the end of the third week. Using light microscopy, lumen patency, intimal and medial damage, inflammation, and granulation were evaluated histopathologically.The mean anastomosis time for the experimental group (15 minutes) was shorter than that for the classic group (mean 21 minutes), and the difference was statistically significant (P < 0.01), while the difference between the patency rates was not significant (P = 0.05). Therefore, provided that the incisions are made correctly, our microvascular anastomosis technique using 3 horizontal mattress sutures can be used in experimental and clinical studies. Copyright © 2006 by Lippincott Williams & Wilkins.
Keywords: 3 Horizontal Mattress Sutures; Microsurgery; Microvascular Surgery; Vascular Anastomosis Method; Vessel Anastomosis